2007
DOI: 10.1021/jf070070q
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Resveratrol and Its Trimethyl and Triacetyl Derivatives with Biomembrane Models Studied by Differential Scanning Calorimetry

Abstract: The interaction of resveratrol (trans-3,5,4'-trihydroxystilbene) and two of its derivatives (3,5,4'-tri-O-methylresveratrol and 3,5,4'-tri-O-triacetylresveratrol) with biomembrane models, represented by dimyristoylphosphatidylcholine (DMPC) multilamellar vesicles (MLV), has been studied by differential scanning calorimetry (DSC). The analysis of MLV prepared in the presence of increasing molar fraction of such compounds has been carried out to reveal their maximum interaction with biomembrane models. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…It has been reported that TMS, due to its lipophilicity, is unable to migrate towards the aqueous medium and interact with biomem- brane model (Sarpietro et al, 2007). Pharmacokinetic studies of TMS formulated with hydroxypropil-␤-cyclodextrins have also been carried out (Lin and Ho, 2009) but nothing has been reported on TMS ability to interact with biomembranes in the presence of ␤-CD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TMS, due to its lipophilicity, is unable to migrate towards the aqueous medium and interact with biomem- brane model (Sarpietro et al, 2007). Pharmacokinetic studies of TMS formulated with hydroxypropil-␤-cyclodextrins have also been carried out (Lin and Ho, 2009) but nothing has been reported on TMS ability to interact with biomembranes in the presence of ␤-CD.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, methylation decreases aqueous solubility and could hinder the oral bioavailability of TMS. In a previous paper (Sarpietro et al, 2007) we compared the interaction and the absorption of resveratrol and two analogs (TMS and 3,5,4 -tri-Otriacetylresveratrol) with biomembrane model. From this study it emerged a strong interaction of TMS with the biomembrane model but a very poor absorption.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve these objectives, we synthesized several analogs possessing phenolic hydroxyl groups together with their methylated congeners. While our work was in progress, a similar, more limited study appeared in the literature where only resveratrol, 3,5,4 0 -tri-O-methylresveratrol, and 3,5,4 0 -tri-O-acetylresveratrol were evaluated (Sarpietro et al 2007). Of special interest are the results reported for resveratrol and its trimethylated analog: (a) Resveratrol caused suppression of the pretransition at all molar fractions used, while with trimethylresveratrol the same effect was observed for concentrations higher than x = 0.015, indicating that it probably localizes in the nonpolar region of the lipid bilayers; (b) Increasing the molar fraction of resveratrol caused a gradual shift towards a lower main phase-transition temperature and broadening of the phase transition, indicating a decrease of the cooperativity of the main transition and the induction of disorder on the structural lipid; resveratrol caused stronger lowering of the phase-transition temperature than trimethylresveratrol, but the latter exerted stronger broadening of the width of the phase transition than the former at x C 0.15; (c) Phase separation was observed for resveratrol at x = 0.09, while trimethylresveratrol did not show a well-defined phase separation; resveratrol was reported to form concentration-rich and concentration-poor domains; (d) Partition studies showed a high percentage of the two molecules in lipid bilayers (90% for resveratrol and 99.16% for the trimethylated analog); (e) Kinetic studies showed that only resveratrol was taken up by the biomembrane model, whereas exogenous uptake of the trimethylated analog was very poor; (f) While the trimethylated analog showed reduced mobility in aqueous medium when it is exogenously incorporated, it is effectively taken up by biomembranes when the aqueous barrier is overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules possessing a phenolic hydroxyl group are localized in the interface of the lipid bilayers, with the phenolic hydroxyl group probably hydrogen-bonding either with the head-group or the glycerol carbonyls. The methylated analogs locate themselves deeper in the hydrophobic region since they lack the anchor for the polar region (Guo et al 2008;Martel et al 1993;Mavromoustakos et al 1991;1995a, b;1996a, b;1999;Sarpietro et al 2007, Yang et al 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the capacity of resveratrol to partition into the lipid bilayers, its possible location within the membrane, and the influence of this compound on the membrane fluidity were investigated by means of derivative spectrophotometry 14 , steady-state and timeresolved spectrofluorimetry 15 , and fluorescence anisotropy measurements 16 . Previous works have shown the effect of resveratrol in membrane model systems [17][18][19][20][21][22][23] . However, the correct location of resveratrol within the membrane and how the biophysical properties of the lipid bilayer are affected by resveratrol remain to be clarified, since there is some controversy in the literature results.…”
Section: Introductionmentioning
confidence: 99%